Solubility and Dissolution Thermodynamic Data of Mefenamic Acid Crystals in Diﬀerent Classes of Organic Solvents - Siti Kholijah, Abdul Mudalip; Mohd R., Abu Bakar; Parveen, Jamal; Fatmawati, Adam (ACS Publications, 2013)
Diﬀerent classes of solvents provide diﬀerent polarity values, which inﬂuence the solubility of pharmaceutical solids. In this article, the solubility of mefenamic acid in diﬀerent classes of organic solvents, including polar protic, dipolar aprotic, and apolar aprotics at a range of temperatures from (298 to 323) K are reported. It has been found that mefenamic acid shows high solubility in dipolar aprotic solvents(N,N-dimethylacetamide, N,N-dimethylformamide, ethyl acetate, and propanone), moderate solubility in polar protic solvents (ethanol and propan-2-ol), and poor solubility in apolar aprotic solvents (hexane, heptane, and cyclohexane) and water.